Identifikasi Permasalahan Remaja dan Implementasi Layanan BK dalam Penanganannya di Madrasah Tsanawiyah Cirebon - Awa Najwa Mardiyah; Azca Nawal Makiyah Hr; Gunawan Gunawan; Uswatun Nabilah; Vanny Dwi Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to explore issues faced by students and the contribution of guidance and counseling (BK) services in addressing various challenges at MTSN Cirebon. The issues studied include low levels of discipline, school withdrawal behavior, lack of learning motivation, and smoking habits among students. This study employed a qualitative, descriptive approach. Participants in the study consisted of BK teachers, students, and student organizations (OSIM and MPK) selected using a purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation. Data analysis was conducted using an interactive model involving data reduction, data presentation, and conclusion drawing. Its validity was tested through triangulation of sources and techniques. The findings of this study indicate that the issues faced by students are influenced by internal and external factors, such as lack of self-awareness, low learning motivation, environmental impacts, and excessive use of social media. BK services play a vital role in addressing these issues through preventive and curative approaches, as well as collaboration between teachers, students, parents, and school organizations. In addition, consistent discipline, engaging learning methods, and monitoring of student behavior are also crucial elements in problem-solving efforts. This research confirms that resolving student issues requires a comprehensive and collaborative approach across all parties within the school environment. Guidance and counseling services play a strategic role in supporting students in overcoming challenges and developing their full potential.